MnN4 Oxygen Reduction Electrocatalyst: Operando Investigation of Active Sites and High Performance in Zinc–Air Battery - Han, Xu; Zhang, Tianyu; Chen, Wenxing; Dong, Bo; Meng, Ge; Zheng, Lirong; Yang, Can; Sun, Xiaoming; Zhuang, Zhongbin; Wang, Dingsheng; Han, Aijuan; Liu, Junfeng (Advanced energy materials, 2021)
The development of inexpensive and highly efficient nonprecious metal catalysts to substitute Pt in the alkaline oxygen reduction reaction is an appealing idea in the energy field. Herein, a Mn oxygen reduction electrocatalyst with a half‐wave potential (E1/2) as high as 0.910 V under an alkaline oxygen reduction reaction process is developed, and the dynamic atomic structure change of the highly efficient Mn single‐atomic site is investigated using operando X‐ray absorption spectroscopy. These results demonstrate that the low‐valence MnL+N4 is the active site during the oxygen reduction process. Density functional theory reveals that facile electron transfer from MnL+N4 to adsorbed *OH species plays a key role in the excellent electrocatalytic performance. Moreover, when assembled as the cathode in a zinc–air battery, this MnN4 material shows high power density and excellent durability, demonstrating its promising potential to substitute the Pt catalyst in practical devices. A manganese single‐atomic‐site catalyst with high performance in the oxygen reduction reaction and zinc–air batteries is reported. Operando X‐ray absorption spectroscopy reveals the formation of inactive high‐valence OHadsMnH+N4 in electrolytes, which progressively switches to active low‐valence MnL+N4 sites under applied potential. Theoretical calculations show that the atomically dispersed structure facilitates the electron transfer from MnN4 to *OH species.